2013
DOI: 10.1673/031.013.3301
|View full text |Cite
|
Sign up to set email alerts
|

A Third Type of Defensive Behavior in the Tenebrionid BeetleZophobas atratusPupae

Abstract: Pupae of the tenebrionid beetle Zophobas atratus Fabricius (Coleoptera: Tenebrionidae) exhibit two types of reflex abdominal motions in response to tactile stimulation: circular rotation and lateral bending to close pinching devices (gin-traps). In the present study, the pupa exhibited novel, sequential abdominal movements at 0.3–2.2 sec after the onset of mechanical stimulation. The most effective stimulation was gentle, double brushing on the ventral surface of an abdominal segment (sternite). The sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The pupae ( Fig. 2C ) are mostly quiescent, however, when tactile stimulated, they have the ability to rotate their abdominal segments in a circular motion ( Ichikawa and Kurauchi 2009 , Ichikawa et al 2012b ) or exhibit other physical responses ( Ichikawa et al 2012a , Ichikawa and Sakamoto 2013 ). All these reactions are considered to be an effective pupal defense mechanism against predator attacks and larval cannibalistic behaviors and are triggered by the stimulation of different types of mechanoreceptive sensilla on the pupal body surface ( Kurauchi et al 2011 ).…”
Section: Identification Key Characteristics and Biologymentioning
confidence: 99%
“…The pupae ( Fig. 2C ) are mostly quiescent, however, when tactile stimulated, they have the ability to rotate their abdominal segments in a circular motion ( Ichikawa and Kurauchi 2009 , Ichikawa et al 2012b ) or exhibit other physical responses ( Ichikawa et al 2012a , Ichikawa and Sakamoto 2013 ). All these reactions are considered to be an effective pupal defense mechanism against predator attacks and larval cannibalistic behaviors and are triggered by the stimulation of different types of mechanoreceptive sensilla on the pupal body surface ( Kurauchi et al 2011 ).…”
Section: Identification Key Characteristics and Biologymentioning
confidence: 99%
“…Previous studies have been documented in the pupae of other species which undergo similar wriggling motion against predators such as Kiwi, Weka, and Rock wren. For instance, Atijebde et al (2020) observed vibrational stimuli-activated defenses in Wiseana viette (Lepidoptera: Hepialidae) pupae; similar behavior was also observed in Zophobas atratus (Coleoptera: Tenebrionidae) beetle pupae ( Grosman et al 2008 ; Ichikawa et al 2012 ; Ichikawa and Sakamoto 2013 ).…”
Section: Discussionmentioning
confidence: 81%
“…This external stimulus can originate from physical presence as well as vibrational signals emitted by enemies which induce antipredatory behavior ( Chandrasegaran et al 2020 ), leading to abdominal movements commonly known as sinusoidal wriggling and lateral bending/up–down forth motion (pulsating events). These responses are a direct result of neuronal activation that culminates in the movement of abdominal segments, turning their dorsum away from the enemy ( Ichikawa and Sakamoto 2013 ). In our study, the observed wriggling and pulsating movement in M. sexta pupae upon the introduction of vibrational signals to the pupal abdomen for 3 s were also an attempt of pupae to turn themselves (by turning their dorsum) away in the wake of an enemy or any warning signals.…”
Section: Discussionmentioning
confidence: 99%